TEACHERS PERCEPTION ON THE UTILIZATION OF CLIL IN TEACHING LITERACY TO YOUNG LEARNERS: A CASE STUDY IN WEST NUSA TENGGARA INTERNATIONAL SCHOOL: TEACHERS’ PERCEPTION ON THE UTILIZATION OF CLIL IN TEACHING LITERACY TO YOUNG LEARNERS: A CASE STUDY IN WEST NUSA TENGGARA INTERNATIONAL SCHOOL - Amalina, Auha; Supriadi , Muhamad (LP2M Institut Agama Islam Nurul Hakim, 2024)
CLIL (Content and Language Integrated Learning) is a dual-focused study focusing on content and language in educating and acquiring materials using the target language. In teaching English to young learners, CLIL is essential in enhancing children's literacy skills. It will enable young learners to understand, acquire, and use information bilingually and ready to face global needs. This study must be implemented due to the need for more research in bilingual education. This study uncovered teachers' perceptions of CLIL implementation in international schools. Through this understanding, the research aims to identify challenges, training needs, and potential solutions to enhance the effectiveness of CLIL in learning. This research employs a qualitative approach with in-depth interviews of several teachers teaching in an international school in West Nusa Tenggara. The research was conducted through observations, document studies, and interviews. These aim to gain an in-depth understanding of CLIL implementation with seven primary teachers in one of the international schools in West Nusa Tenggara. Data analysis was conducted using a thematic approach to identify patterns, themes, and perspectives in their perceptions. Conclusion and implication were drawn from the discussion of the findings.